Crystal structure and theoretical study of (2E)-1-[4-hydroxy-3-(morpholin-4-ylmethyl)phenyl]-3-(thiophen-2-yl)prop-2-en-1-one - Yesilyurt, Fatma; Aydin, Abdullah; Gul, Halise Inci; Akkurt, Mehmet; Ozcelik, Nefise Dilek (International Union of Crystallography (IUCr), 2018)
In the title compound, C18H19NO3S, the morpholine ring adopts a chair conformation. The thiophene ring forms dihedral angles of 26.04 (9) and 74.07 (10)° with the benzene ring and the mean plane of the morpholine ring, respectively. The molecular conformation is stabilized by an O—H...N hydrogen bond. In the crystal, molecules are connected through C—H...O hydrogen bonds, forming wave-like layers parallel to the ab plane, which are further linked into a three-dimensional network by C—H...π interactions involving the benzene rings and the methylene H atoms of the morpholine rings.
Keywords: crystal structure; HOMO; LUMO; Crystallography; chalcones; theoretical study; Theoretical Study; quantum-chemical calculation; Research Communications; Mannich Bases; quantum-Chemical Calculation; Chalcones; QD901-999; Mannich bases; Crystal Structure; 3. Good health